RELATIONALITY ACROSS EAST AND WEST - Kwak, Chun-hyŏk.; Cheng, Ken. ([S.l.] : ROUTLEDGE, 2025)
This book explores how the concept of relationality' can offer a strong basis for cross-cultural dialogue between Western and non-Western traditions of moral and political philosophy. As addressed in this book, the implications of relationality go beyond a Eurocentric binary of Western individualism and non-Western collectivism. Instead, the contributors seek to establish an appropriate discursive stance for understanding and deliberating over relationality across cultural boundaries. Through an investigation of the theoretical and practical meanings of relationality across East and West, it offers possible frameworks for reconciling the emphasis on individual choice in modern Western social and political philosophy with the amorphous dynamics of relational morality in non-Western philosophical discourses. Examining relationality in practical forms and culturally-situated contexts, rather than positing an essentialist view of the relational self, this book will be of interest to scholars in political philosophy, intellectual history, contemporary political theory and Northeast Asian regional studies.
Keywords: Ethics -- History; PHILOSOPHY / Political; POLITICAL SCIENCE / History & Theory